2004
DOI: 10.1084/jem.20031639
|View full text |Cite
|
Sign up to set email alerts
|

Senescent Impairment in Synergistic Cytokine Pathways That Provide Rapid Cardioprotection in the Rat Heart

Abstract: Pretreatment of rodent hearts with platelet-derived growth factor (PDGF)–AB decreases myocardial injury after coronary occlusion. However, PDGF-AB cardioprotection is diminished in older animals, suggesting that downstream elements mediating and/or synergizing the actions of PDGF-AB may be limited in aging cardiac vasculature. In vitro PDGF-AB induced vascular endothelial growth factor (VEGF) and angiopoietin (Ang)-2 expression in 4-mo-old rat cardiac endothelial cells, but not in 24-mo-old heart cells. In viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…To this end, we have previously demonstrated that the delayed kinetics of PDGF-AB-mediated cardioprotection can be eliminated by the codelivery of PDGF-AB and the growth factors downstream from PDGF-AB in cardiac angiogenic pathways at the time of acute coronary occlusion to act synergistically to reduce cardiac cell death and decrease myocardial injury (27). Indeed, the significant increase in TUNEL staining after PDGF-AB injection in the old IPC rats is consistent with the diminished survival of this treatment group after permanent LAD occlusion compared with the rats receiving IPC alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we have previously demonstrated that the delayed kinetics of PDGF-AB-mediated cardioprotection can be eliminated by the codelivery of PDGF-AB and the growth factors downstream from PDGF-AB in cardiac angiogenic pathways at the time of acute coronary occlusion to act synergistically to reduce cardiac cell death and decrease myocardial injury (27). Indeed, the significant increase in TUNEL staining after PDGF-AB injection in the old IPC rats is consistent with the diminished survival of this treatment group after permanent LAD occlusion compared with the rats receiving IPC alone.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, codelivery of platelet-derived growth factor (PDGF)-AB can reverse these impairments and restores cardioprotection to the aging heart. Mechanistically, the actions of PDGF-AB are mediated in combination with its induction of both vascular endothelial growth factor (VEGF) and angiopoietin (Ang)-2 (but not VEGF and Ang-2 without PDGF-AB) to acutely suppress apoptosis and reduce myocardial infarction (27). From these findings, we hypothesized that strategies targeting PDGF-AB-based pathways (PDGF-AB alone or in combination with VEGF and Ang-2) would improve functional outcomes under conditions associated with dysregulation of TNF-␣-mediated cardioprotection in the aging heart.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the injurious potential of inflammatory mediators in patients with myocardial infarction may have been overstated due to extrapolation from young animals to human patients. In addition, senescent ischemic hearts show impairment of important cardioprotective pathways involving TNF-α [339] and PDGF-AB [340] and have a decreased anti-apoptotic response to administration of GranulocyteColony Stimulating Factor (G-CSF) and SCF [341] in comparison with young animals.…”
Section: Do Anti-inflammatory Approaches Reduce Cardiomyocyte Injury?mentioning
confidence: 99%
“…Specifically, we hypothesized that studies in the pinnal allograft model would identify the vascular/endothelial compartment(s) that underlie the diabetic impairment in cardiac vascular function. Indeed, because this model has facilitated the advancement of novel cardioprotective approaches (7,29), the results of pinnal allograft studies in diabetic mice could direct the development of molecular-and/or cellularbased approaches that may reduce diabetic-related cardiovascular diseases.…”
mentioning
confidence: 99%